PENGARUH FERMENTASI TERHADAP PENDAPATAN PETANI KAKAO DI DESA WAWONGGOLE KECAMATAN WONGGEDUKU KABUPATEN KONAWE - Hasniati Hasniati (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
This study aims to determine the effect of cocoa bean fermentation on farmers' income in Wawonggole Village, Wonggeduku District, Konawe Regency. Determination of the location is done intentionally (purposive) on the basis of the consideration that the area is quite potential for agricultural development, especially cocoa. The population in this study were 78 farmers working on cocoa plants. Sampling is done by cluster random sampling, the population is grouped into 2 (two), namely farmers who carry out fermentation as many as 48 people and farmers who do not carry out fermentation as many as 30 people and each group randomly selected samples, the number of samples determined by using the Slopin formula at 10% accuracy, the number of samples taken was 32 people who carried out fermentation and 23 people who did not carry out fermentation. With the testing criteria, the F Test is used to determine whether the regressor variable has a real effect on the regression variable. Based on the results of the study shows that the production variable, the area of ​​arable land and the use of fermentation technology simultaneously (together) have a very real influence on farm income cocoa